Influence of Arabic Knowledge on The Understanding of Islamic Studies among Secondary School Students in Kwara State, Nigeria - Olalekan Rasheed Azeez; Ibrahim Solahudeen Owoyale-Abdulganiy (Jurnal Pendidikan : Riset dan Konseptual, 2025)
The study examined the influence of Arabic knowledge on the understanding of Islamic Studies among secondary school students in Kwara State, Nigeria. Descriptive research design of survey type was used in the study. Population of the study was all secondary school Islamic Studies students in Kwara State. Simple random sampling technique was used in the study to select the sample. The instrument used in the study was developed by researchers themselves and it was titled “influence of Arabic knowledge on the understanding of Islamic Studies” (IAKUIS). Percentage was used to answer all research questions raised in the study. The finding of study revealed that the influence of Arabic knowledge on the understanding of Islamic Studies among secondary school students in Kwara State was high. The study concluded that Arabic knowledge influence understanding of Islamic Studies among secondary school students in Kwara State, Nigeria. Therefore, the study recommended that Islamic Studies teachers should encourage secondary school students of Islamic Studies to add Arabic knowledge to their understanding of Islamic Studies.